Separate Feeding Between the Pelagic Stage of the Squat Lobster Munida gregaria and the Larger Sized Zooplankton Crustacean Groups in the Beagle Channel as Revealed by Stable Isotopes - Castro, Leonardo R.; González, Humberto E.; Garcés-Vargas, José; Barrientos, Pamela (Frontiers in Marine Science, 2021)
The Beagle channel, in southern Patagonia, shows very low production during winter but, at the same time, sustains very dense aggregations of the pelagic stages of squat lobster (Munida gregaria), a benthic decapod whose juveniles have the largest body size within the chitinous pelagic community. To assess how do the mesozooplankton community and the pelagic M. gregaria stages manage to coexist under the harsh feeding winter conditions, we conducted a research cruise at two locations connected to the Beagle Channel, Yendegaia Bay (land terminating-glacier) and Pia Fjord (marine-terminating glacier). Our results show that the zooplankton community was similar in these two fjords, that a single pelagic group dominated in terms of biomass (Munida gregaria), and that differences in vertical distribution existed among the principal crustacean zooplankton groups. All groups showed consumption of terrestrially derived organic matter, as revealed by their δ13C values. However, the isotopic composition, trophic positions (TP) and isotopic niche areas of the groups clearly separated pelagic M. gregaria presenting the later some of the lowest δ15N and the highest δ13C values, and the narrowest isotopic niche width. This group was dominated by a single body size class along the 0-100 m water column, did not show diel vertical migrations (DVM) and remained mostly in the upper layers (0-50m) apparently benefiting from the higher phytoplankton concentrations, as revealed by their higher δ13C values and low trophic position. In contrast, the other groups developed DVM or remained deeper in the water column, and showed higher δ15N values, higher TP and lower δ13C values, most of them probably feeding on a nanoheterothrophs-terrestrial particulate organic matter mixture at deeper layers. Thus, the different vertical distributions, DVM patterns, different trophic level food sources and slightly different organic carbon sources, apparently reduced any potential competence for food resources and form part of the feeding strategy that may facilitate the coexistence of the different large pelagic crustaceans under the harsh feeding winter conditions at this high latitude region.